Implementasi Pengelolaan Arsip pada Bidang Pembinaan dan Pengawasan di Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Sidoarjo - Deasy Rizki Masruroh; Magda Faradiba Mauludia Agung (Pusat Riset dan Inovasi Nasional, 2026)
Proper archives management is a fundamental requirement in government administration systems to ensure the availability of authentic and accountable information. This community service activity aims to improve the quality of archives management in the Development and Supervision Sector at the Community and Village Empowerment Service of Sidoarjo Regency through technical assistance in archives arrangement. The method used was a qualitative descriptive approach with stages including initial condition observation, coordination with partners, and implementation of technical actions including document sorting, packaging into boxes, labeling with uniform format, and arrangement in storage rooms. The results showed a change in conditions from irregularly piled archives to organized archives in labeled boxes with consistent identities, thereby improving ease of retrieval and access control of archives. This activity also established new work practices in the form of sorting habits, uniform labeling, and recorded lending mechanisms. The implication of this activity is the formation of a foundation for a more transparent and accountable archives management system, although it still requires improvement through the preparation of archive lists per box and alignment with the official archive classification code of Sidoarjo Regency Government.